Effect Physical Activity and Nutrition During The Covid-19 Pandemic - Dharma Utamayasa, I Gede (Malikussaleh University, Aceh, Indonesia, 2021)
The main key in fighting the corona virus is to always maintain endurance and be balanced with maximum nutritional intake. With regular nutritional intake and exercise, immunity will be maintained so that children who are able to ward off disease, if already healing will be faster. Nutritional problems that occurred during the pandemic resulted from changes in adolescent habits, especially in physical activity. This study aims to prove the relationship between physical activity and nutritional status in elementary school children N 1 Kaliuntu. This type of research is a survey. The target population is primary school children aged 7-9 years which means 30 students. The first data during the pandemic was 33% and the proportion of the nutritional status of very thin, thin, obese and obese elementary school students was 29.9%. The second data shows that there is a relationship between physical activity during the Covid-19 pandemic and the nutritional status of elementary school children at primary school N 1 Kaliuntu.